Orientation control of intermediate-composition SiGe on insulator by low-temperature Al-induced crystallization. (September 2016) - Nakata, Mitsuki; Toko, Kaoru; Saitoh, Noriyuki; Yoshizawa, Noriko; Suemasu, Takashi
Abstract: Metal-induced crystallization has allowed for high-quality Si and Ge thin films on insulators at low temperatures; however, there has been difficulty for SiGe alloys of intermediate compositions. Here we demonstrate a large-grained (> 100 μm), 99% (111)-oriented Si0.4 Ge0.6 layer on a glass substrate through layer exchange between Al and amorphous Si0.4 Ge0.6 layers. Slow annealing below 350 °C is a key to suppressing nucleation and facilitating lateral growth. The use of the (111)-oriented SiGe layers as epitaxial templates will pave the way for integrating various materials monolithically on three-dimensional Si large-scale integrated circuits and on multi-functional displays. Graphical abstract: Al-induced layer exchange allows for a 99% (111)-oriented SiGe thin film with an intermediate composition on a glass substrate. Slow annealing below 350 °C is a key for large-grain growth: it suppresses nucleation and facilitates lateral growth during the crystallization of the amorphous Si0.4 Ge0.6 alloy.